Training and Counseling on Stock Opname Bookkeeping at Saung Injuk Restaurant, Bandung Regency - Erislan Erislan (Syntax Corporation Indonesia, 2024)
Community Service Activities that provide counseling on the importance of bookkeeping and training on bookkeeping and hospitalization recording for all incoming and outgoing goods activities to maintain the continuity of stock and raw material availability as well as cost efficiency efforts. The outcome that can be realized from this Community Service activity is that actors are able to carry out bookkeeping and recording of their business regularly by using hospitalization recording and calculating cost efficiency. Recording of stock-taking. As a result,